COMPLEX THERAPY OF ENDEMIC GOITTER WITH THE APPLICATION OF PHYTO- AND VITAMIN THERAPY IN CHILDREN (American Journal of Technology and Applied Sciences, 2024)
Endemic goiter is one of the most common non-communicable diseases in the world. Against the background of the disease, there is a dysfunction of the gastrointestinal tract, reproductive function in women, physical and mental development, immunological deficiency, arterial hypertension, atherosclerosis, etc. 117 students of Samarkand State University aged 18 to 25 years were studied. patients were divided into 2 groups: group I (57 patients) – received traditional treatment (iodine preparations), group II (60 patients) – received herbal and vitamin therapy against the background of traditional treatment. Complex treatment of patients with endemic goiter using herbal and vitamin therapy to restore impaired intestinal absorption helps to improve the absorption of iodine and is an effective method of therapy.